Can context undo constructional meaning? A Construction Grammar study of French en situation de + NOUN - Sophie Raineri (CogniTextes, 2024)
This article investigates the extent to which context can impact the meaning of a construction. It focuses on the French expression en situation de (‘in situation of’) + NOUN, whose meaning is contested among language users when specifically applied to human referents (e.g., en situation de handicap ‘disabled’, en situation de pauvreté ‘poor’). Analyzed as a constructional idiom, its meaning is mapped out on the basis of corpus data. Although a clash is consistently observed between the “circumstantial characterization” meaning arising from the constituent parts of the construction and the “inherent characterization” interpretation it typically receives in context, I argue that contextual pressure has not resulted in the obliteration of constructional meaning. En situation de + NOUN is shown to retain semantic and pragmatic properties that distinguish it from referentially equivalent expressions and ensure its longevity. In addition to making a contribution to research on euphemism and so-called ‘politically correct’ language, the article demonstrates the necessity to uphold the semantics/pragmatics distinction in usage-based Contruction Grammar (CxG) studies of language and language change.